High magnetostriction parameters for low-temperature sintered cobalt ferrite obtained by two-stage sintering - Mohaideen, Kamal Khaja; Joy, Pattayil Alias (Journal of Magnetism and Magnetic Materials, 2014)
From the studies on the magnetostriction characteristics of two-stage sintered polycrystalline CoFe2O4 made from nanocrystalline powders, it is found that two-stage sintering at low temperatures is very effective for enhancing the density and for attaining higher magnetostriction coefficient. Magnetostriction coefficient and strain derivative are further enhanced by magnetic field annealing and relatively larger enhancement in the magnetostriction parameters is obtained for the samples sintered at lower temperatures, after magnetic annealing, despite the fact that samples sintered at higher temperatures show larger magnetostriction coefficients before annealing. A high magnetostriction coefficient of similar to 380 ppm is obtained after field annealing for the sample sintered at 1100 degrees C, below a magnetic field of 400 kA/m, which is the highest value so far reported at low magnetic fields for sintered polycrystalline cobalt ferrite. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Cobalt ferrite; Magnetostriction; Two-stage sintering